2015
DOI: 10.1002/jclp.22189
|View full text |Cite
|
Sign up to set email alerts
|

Anger Rumination as a Mediator of the Relationship Between Mindfulness and Aggression: The Utility of a Multidimensional Mindfulness Model

Abstract: Nonjudgment and present-centered awareness may influence aggression via reduced anger rumination. The importance of examining mindfulness as a multidimensional construct is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
57
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 63 publications
13
57
1
2
Order By: Relevance
“…Our use of a global measure of mindfulness also precludes assessing whether different aspects are uniquely associated with traumatic symptoms. This is important to consider in future studies as one study found that it was mostly high levels of the non-judging component of mindfulness, but not the observing and acting with awareness components, that predicted less anger rumination and, in turn, less anger Running head: SEXUAL ABUSE OR ASSAULT AND MINDFULNESS 17 and aggression (Peters et al 2015). Other mindfulness-related constructs not assessed in the current study (e.g.…”
Section: Recommendationsmentioning
confidence: 68%
“…Our use of a global measure of mindfulness also precludes assessing whether different aspects are uniquely associated with traumatic symptoms. This is important to consider in future studies as one study found that it was mostly high levels of the non-judging component of mindfulness, but not the observing and acting with awareness components, that predicted less anger rumination and, in turn, less anger Running head: SEXUAL ABUSE OR ASSAULT AND MINDFULNESS 17 and aggression (Peters et al 2015). Other mindfulness-related constructs not assessed in the current study (e.g.…”
Section: Recommendationsmentioning
confidence: 68%
“…Authors also conclude that more advanced practitioners could be able to develop both types of regulation. Recent research by Peters et al (2015) also pointed to a signiÞ cant positive relationship between mind wandering and aggression, suggesting that lowering rumination through mindfulness actually leads to reduction of anger. Development of mindfulness for the purpose of better coping with stress and other negative emotions seems to be especially crucial in leadership as some authors suggest a leader's emotional state to be easily distributed on followers (Boyatzis & McKee, 2005).…”
Section: Challenges Of Contemporary Organizationsmentioning
confidence: 99%
“…Research in positive psychology has shown that altruistic behaviour has a positive influence on various psychological outcomes (Nelson et al 2015;Ouweneel et al 2014;Weinstein and Ryan 2010). Furthermore mindfulness has been shown to reduce rumination, significantly reducing aggressive behaviour, and depressive symptoms (Borders et al 2010;Eisenlohr-Moul et al 2016;Heeren and Philippot 2011;Heppner et al 2008;Hwang and Kearney 2013;Labelle et al 2010;Peters et al 2015;Rodriguez et al 2014;Yusainy and Lawrence 2015), in addition to many of its other well-known benefits (Creswell 2017;Gotink et al 2015;Paulus 2016).…”
Section: Factors Affecting the Flow Of Experiencementioning
confidence: 99%